2007
DOI: 10.1534/genetics.106.066597
|View full text |Cite
|
Sign up to set email alerts
|

Cis-Regulatory Elements in the Accord Retrotransposon Result in Tissue-Specific Expression of the Drosophila melanogaster Insecticide Resistance Gene Cyp6g1

Abstract: Transposable elements are a major mutation source and powerful agents of adaptive change. Some transposable element insertions in genomes increase to a high frequency because of the selective advantage the mutant phenotype provides. Cyp6g1-mediated insecticide resistance in Drosophila melanogaster is due to the upregulation of the cytochrome P450 gene Cyp6g1, leading to the resistance to a variety of insecticide classes. The upregulation of Cyp6g1 is correlated with the presence of the long terminal repeat (LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
263
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(268 citation statements)
references
References 45 publications
5
263
0
Order By: Relevance
“…These include the P450s involved in the synthesis of ecdysone, Cyp302a1, Cyp306a1, Cyp307a2, Cyp314a1, and Cyp315a1. Cyp6g1 is detected in the midgut and Malpighian tubules in both feeding and wandering third instar larvae, with additional expression detected in the fat body of wandering larvae (49). Expression for a subset of these P450s was confirmed by semiquantitative PCR (SI Methods; Fig.…”
Section: Some P450 Show Differential Expression Between Feeding and Wan-mentioning
confidence: 83%
See 2 more Smart Citations
“…These include the P450s involved in the synthesis of ecdysone, Cyp302a1, Cyp306a1, Cyp307a2, Cyp314a1, and Cyp315a1. Cyp6g1 is detected in the midgut and Malpighian tubules in both feeding and wandering third instar larvae, with additional expression detected in the fat body of wandering larvae (49). Expression for a subset of these P450s was confirmed by semiquantitative PCR (SI Methods; Fig.…”
Section: Some P450 Show Differential Expression Between Feeding and Wan-mentioning
confidence: 83%
“…S1). Nine P450s are detected in the fat body, including the previously characterized Cyp6g1, Cyp12d1, and Cyp314a1 (22,40,49). Cyp4p2 and Cyp4s3 are the only P450s detected exclusively in the fat body.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Our data show that these insertions in Cyp genes carry putative TFBSs, which reinforces the hypothesis that they might play important roles in the adaptation of Drosophila species. These particular characteristics may explain why TEs interfere in the transcription of some Cyp genes by elevating their expression levels (Catania et al, 2004;Chung et al, 2007;Daborn et al, 2002). Empirical studies involving transfection and expression experiments for these putative regulatory sequences can corroborate the hypothesis that DNAREP1 sequences have been domesticated to contribute to new, alternative transcription start sites in Drosophila genomes.…”
Section: Discussionmentioning
confidence: 76%
“…Daborn et al (2002) reported that the insecticide resistance mapping to the DDT-R locus of D. melanogaster is due to the over-expression of one gene, Cyp6g1, and that a single Cyp6g1 allele linked to this resistance is distributed worldwide. Unlike other insecticide resistance genes in which overexpression is associated with point mutations, over-expression of Cyp6g1is characterized by the insertion of a fragment of the Accord retrotransposon upstream of the gene (Catania et al, 2004;Chung et al, 2007;Daborn et al, 2002). Schlenke and Begun (2004) have also reported an association between a TE insertion and insecticide resistance in Drosophila simulans.…”
Section: Introductionmentioning
confidence: 99%